DESIGN AND DEVELOPMENT OF NOSOCOMIAL INFECTION VISUALIZATION APPLICATION IN HUSADA UTAMA HOSPITAL SURABAYA - Arifin, Alrafif Naufal Ghani; tiowati, Sulis; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
The process of nosocomial infection surveillance at the Husada Utama Hospital in Surabaya is still using a manual process. By distributing the surveillance forms every day at around 12:00 WIB to the rooms where inpatients are treated. The problems that occur are as follows: repeated recording from room nurses, IPCN and PPI Units, making special reports that are still manual, and frequent errors in copying data from surveillance forms.               The solution offered in this research is to make a visualization application design for nosocomial infection surveillance, with the problems: conducting surveillance, making special reports addressed to IPCN by providing information on conditions and symptoms of infection through the application, can reduce the recording process that occurs as much as 3 times, and conduct monitoring to monitor infection control at the Husada Utama Hospital in Surabaya.               The results of trials that have been carried out indicate that this application can complete the process of recording surveillance, recording and preparing special reports. PPI Unit is also assisted in the monitoring process by displaying information on surveillance events in the form of charts in the form of charts periodically and real time.